Cross Border Banking Supervision : Incentive Conflicts in Supervisory Information Sharing between Home and Host Supervisors - D'Hulster, Katia (2012)
The global financial crisis has uncovered a number of weaknesses in the supervision and regulation of cross border banks. One such weakness was the lack of effective cooperation among banking supervisors. Since then, international bodies, such as the G-20, the Financial Stability Board and the Basel Committee have actively promoted the use of supervisory colleges. The objective of this paper is to explore the obstacles to effective cross border supervisory information sharing. More specifically, a schematic presentation illustrating the misalignments in incentives for information sharing between home and host supervisors under the current supervisory task-sharing anchored in the Basel Concordat is developed. This paper finds that in the absence of an ex ante agreed upon resolution and burden-sharing mechanism and deteriorating health of the bank, incentive conflicts escalate and supervisory cooperation breaks down. The promotion of good practices for cooperation in supervisory colleges is thus not sufficient to address the existing incentive conflicts. What is needed is a rigorous analysis and review of the supervisory task-sharing framework, so that the right incentives are secured during all stages of the supervisory process. For this purpose, it is essential that policy makers integrate and harmonize the current debates on crisis management, resolution policy and good supervisory practices for cross border banking supervision.